Application Of Artificial Intelligence To Diagnose Tiger Prawn Diseases (Penaeus Monodon) Using The Mamdani Fuzzy Logic Model Method - Azahra, Syafira Dinka; Alif Diaz Ibramahesa; Siti Zalfa Fadillah; Abrisam Hadi Bintoro; Indy Widyanti; Muhammad Jerri; Monic Hapsari; Muhammad Yasir Anwar; Shadam Dwi Permana; Rhaihany Aliefia D R; R Riza Pamungkas S; Khaerunisa Agustina; Nanda Octavia; Ester Angeline; Muhammad Danang Mukti Darmawan; Fiqri Nurfadillah; Wiyoto Wiyoto; Ridwan Siskandar (Jurnal Sains Indonesia, 2024)
Diseases in black tiger shrimp are crucial to monitor for their survival and productivity in aquaculture. Rapid detection through clinical symptoms, though not 100% accurate, is vital for prompt action. This study aims to diagnose diseases in black tiger shrimp using computer-based artificial intelligence based on observational input. A qualitative data analysis method is employed, with variables including clinical symptoms, eye damage, and body color change. Results show that body damage is the most influential factor in disease type. Although fuzzy logic is not 100% accurate, it is essential and beneficial for shrimp farmers.